2017
DOI: 10.1038/ncomms15584
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic IL-6 and IL-8 paracrine signalling pathway infers a strategy to inhibit tumour cell migration

Abstract: Following uncontrolled proliferation, a subset of primary tumour cells acquires additional traits/mutations to trigger phenotypic changes that enhance migration and are hypothesized to be the initiators of metastasis. This study reveals an adaptive mechanism that harnesses synergistic paracrine signalling via IL-6/8, which is amplified by cell proliferation and cell density, to directly promote cell migration. This effect occurs in metastatic human sarcoma and carcinoma cells– but not in normal or non-metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 57 publications
9
154
0
1
Order By: Relevance
“…Similar results have been reported by Jayatilaka et al, 6 and they found that the metastatic cancer cell lines HT1080, MDA-MB-231, and U-87 acquired enhanced migration and invasion abilities due to increased cell density in 3D collagen matrices. Then, the same numbers of cells from the dense or sparse cultures were tested in proliferation, migration, and invasion assays.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results have been reported by Jayatilaka et al, 6 and they found that the metastatic cancer cell lines HT1080, MDA-MB-231, and U-87 acquired enhanced migration and invasion abilities due to increased cell density in 3D collagen matrices. Then, the same numbers of cells from the dense or sparse cultures were tested in proliferation, migration, and invasion assays.…”
Section: Introductionsupporting
confidence: 90%
“…JAM-1 was decreased in samples from dense cultures, which was verified by a western blot. 6 IL-6 and IL-8 are two cytokines that are amplified by cell proliferation and cell density to promote cell migration directly. 24 However, it was reported that the downregulation of JAM-1 in cancer cells can lead to metastasis and poor survival.…”
Section: Figurementioning
confidence: 99%
“…MMP‐9, an enzyme secreted by various tumor cells,1, 25, 26 including B16F10 cells,27, 28, 29 can degrade the extracellular matrix, facilitate detachment and invasion, and enhance tumor cells entry into blood vessels. Thus, TOS can inhibit the beginning of the metastatic cascade, which is a crucial stage of metastasis 30. Based on the above, we constructed a simple self‐delivering micellar NP consisting of the antimetastatic components LMWH and TOS, which inhibit different phases of the metastatic cascade ( Scheme 1 C).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the key proteins and organelles that play a critical role in conventional 2D migration do not necessarily play a significant role in 3D migration and vice versa. For instance, the Arp2/3 complex-based module for dendritic assembly of F-actin and the associated regulatory/activator proteins such as N-WASP and Cdc42 have remarkably different effects on cell migration in 2-and 3D environments (5,10). Similarly, focal adhesion proteins, such as vinculin and p130Cas, play critical roles in 3D migration that are not necessarily predicted by the 2D case (5,11,12).…”
mentioning
confidence: 99%